Urban Indian healthcare referral system: A qualitative exploration from the physicians’ perspectives - Maria Sabastin Sagayam; Priya Gupta; Ram Ramesh; Angan Sengupta (PLoS ONE, 2025)
Background The Indian healthcare system continues to remain unstructured leading to sub-optimal health outcomes, not just in rural but even in urban areas. While physicians play a crucial role in shaping treatment trajectories and managing the referral process, their perspective on the referral system has received very limited academic attention in India. This study attempts to understand the archetypical physician’s referral mechanism and the factors influencing their referral practices. This study also highlights the challenges and possible solutions in operationalising an efficient referral process as suggested by the professionals. Methods In-depth qualitative interviews were conducted with sixty-two physicians consisting of both general physicians and specialists from 19 different disciplines, associated with public and private hospitals in Bengaluru, India. The data, thus collected, was subjected to thematic analysis to generate relevant themes. Results Five themes emerged from the thematic analysis from a phenomenological perspective based on the physicians’ lived experience. First of all, specialist physicians’ availability, accessibility, experience, and reputation strongly influenced referral recommendations. It was also observed that due to lack of a comprehensive healthcare provider database, personal connections and professional networks are utilised. Moreover, although physicians prioritize patients’ affordability and accessibility factors, referral counselling and caregiver-patient communication remained inadequate and required formalization. While the fourth theme clusters around several barriers related to communication, system inefficiencies, lack of awareness, accessibility and affordability among patients; the final theme suggests that the physicians emphasized on urgent need for clear guidelines, regulations and policies to streamline and monitor the referral system. Conclusion This research highlights that physicians recognize the systemic gaps leading to unsolicited health outcomes; yet they are helpless in most cases. The participants emphasized that robust information systems connecting all relevant stakeholders are essential. The exploration reveals that the system will not adopt a structured referral method without the government taking interest in it.